Investigating the Clinical Characteristics and PITX3Mutations of a Large Chinese Family with Anterior Segment Mesenchymal Dysgenesis and Congenital Posterior Polar Cataract - Hui Dang; Min Peng; Weiyue Gu; Gang Ding; Yuqin Sun; Zhongkai Hao; Ning Wei; Xu Wang; Chenming Zhang; Aijun Deng (Journal of Ophthalmology)
Objective. To investigate the clinical characteristics and pathogenic genetic mutations of a Chinese family with anterior segment mesenchymal dysgenesis and congenital posterior polar cataract. Methods. Through family investigation, the family members were examined via slit lamp anterior segment imaging and screened for eye and other diseases by eye B-ultrasound. Genetic test was performed on the blood samples of the fourth family generation (23 people) via whole exome sequencing (trio-WES) and Sanger sequencing. Results. Among the 36 members in four family generations, there were 11 living cases with different degrees of ocular abnormalities, such as cataracts, leukoplakia, and small cornea. All patients who received the genetic test had the heterozygous frameshift mutation c.640_656dup (p.G220Pfs∗95) on exon 4 of the PITX3 gene. This mutation was cosegregated with the clinical phenotypes in the family and thus might be one of the genetic factors that cause the corresponding ocular abnormalities in this family. Conclusion. The congenital posterior polar cataract with or without anterior interstitial dysplasia (ASMD) of this family was inherited in an autosomal dominant manner, and the frameshift mutation (c.640_656dup) in the PITX3 gene was the cause of ocular abnormalities observed in this family. This study is of great significance for guiding prenatal diagnosis and disease treatment.